Philomena: um olhar arqueogenealógico sobre processos de subjetivação/objetivação da mulher irlandesa no século XX - Jesus, José Eduardo Santos Tavares de (2021)
Between the 18th and 20th centuries, the Magdalena Laundry, institutions linked mostly to Catholic congregations, were installed in several countries around the world as shelters for the rehabilitation of fallen women: young victims of rape, orphans, prostitutes, girls accused of abortion or infanticide, single mothers. In Ireland, more precisely after the recognition of the independence of the Irish Free State, in 1922, these reformatories began to fulfill a prison, punitive function, punishing, above all, women who became pregnant outside of marriage, due to the fact that the new State's constitution made maternity and marriage inseparable and connected. One of these inmates had her life portrayed in the biographical film Philomena (FEARS, 2013), the object of our investigation. In the light of archaeogenealogy, the present work seeks, as a general objective, to discursively analyze the aforementioned film, in order to observe which process of subjectivation the protagonist is subjected to, by having her body objectified in some ways. As for the theoretical contribution, as our object of study is a product of the cinematographic media, we resorted to the teachings of Deleuze (2015) and Foucault (2021) about the dispositif. In this way, we treat cinema, in this dissertation, as a network that interconnects numerous elements of different natures; able to manipulate, given its strategic function, the power relations, the productions of subjectivities, and, consequently, the present history, with a view, above all, to a normalization. In this sense, once observed the strong speeches' and subjects’ controls, both in the process of creating the film and in the narrative development itself, we bring to light Foucault's (1996) thesis about the existence, in all societies, of procedures of discursive rarefaction, among which we highlight authorship; from the rarefaction of subjects, the doctrine, the societies of discourse; apart from the interdiction procedures, concerning the part of the speech that puts desire and power into play. Furthermore, to investigate the relationship between discourse and religion, we initially started from the concept that Bourdieu (2007) formulates for this, namely: language, vehicle of power, symbolic-structuring, which makes it possible to create and impose a system of practices, of the world's representations, about the faithful. From this perspective, the religious discourse is conceived as one oriented towards indoctrination. Then, we present the Foucault's lessons ([1978] 2008; 2006) referring to the pastoral of souls, a power of a religious type, characterized by being beneficent, sacrificial, individualizing and totalizing; the institutionalization of the pastorate within the scope of Christianity, an event that marks the implantation, by the Church, of this type of power in the West, through a series of techniques aimed at the domain of subjects, mainly through their sexuality – an example of which is the confession: production of truths from/about the individual, in a testimony against himself. We also use the postulates of Foucault ([1976] 2010; 2014) about the intertwining of two technologies of power within normalization societies, they are: (i) the discipline, centered on the man-machine, which works in order to optimize , at the level of detail, the operations of the body in its relation to work, to produce useful, politically docile individuals; (ii) biopolitics, focused on the man-species, which acts, at the mass level, on a bundle of collective phenomena, considered over a long period of time, in order to produce a regulated population. From this same philosopher, we still work with the notion of modern racism, a resource present in States where biopower is exercised, responsible for the permissibility of murder, whether direct or indirect, of the degenerated, the abnormal, those responsible for the taint of race. Finally, we close our study on the Magdalene asylums, bringing to light Sixsmith's (2013) discussions about the functioning of these institutions in Ireland; those of Smith (2007) relating to the Nation's Containment Architecture.